2009
DOI: 10.1002/elps.200800721
|View full text |Cite
|
Sign up to set email alerts
|

A novel method developed for acetylcholine detection in royal jelly by using capillary electrophoresis coupled with electrogenerated chemiluminescence based on a simple reaction

Abstract: A novel method for highly sensitive detection of acetylcholine in royal jelly was proposed by using CE coupled with electrogenerated chemiluminescence (ECL). Acetylcholine, which could not react with Tris(2,2'-bipyridine)ruthenium(II) to strengthen its ECL signals, decomposed into trimethylamine and strengthened the ECL signals sharply when it was heated to its melting point. This reaction needed no additional reagent and it was mild, simple, stable and rapid, without any side reaction. By combining the above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…To investigate the calcium signaling pathway involved in this elevation, the effects of possible factors found in RJ were examined [27], [28], [29]. An elevation in [Ca 2+ ]i was not detected in 10-HDE (Fig 4B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the calcium signaling pathway involved in this elevation, the effects of possible factors found in RJ were examined [27], [28], [29]. An elevation in [Ca 2+ ]i was not detected in 10-HDE (Fig 4B).…”
Section: Resultsmentioning
confidence: 99%
“…Acetylcholine, a major neurotransmitter involved in tear secretion, was found of 1 mg/g in RJ [27] and increases intracellular Ca 2+ levels by activating muscarinic receptors. 10-hydroxy-2-decenoic acid is a unique fatty acid found in RJ that induces the entry of extracellular Ca 2+ by activating Ca 2+ -permeable nonselective cation channels [28].…”
Section: Discussionmentioning
confidence: 99%
“…This scenario raises the possibility that RJ contains longevity-promoting agents for queens [17], [19]. An analysis of its chemical composition showed that RJ comprises proteins, sugars, lipids, vitamins and free amino acids [20] together with a variety of bioactive substances, including AMP N1-oxide [21], peptides [22][24], acetylcholine [25]–[27] and fatty acids, such as 10-hydroxy-2-decenoic acid (10-HDA) [28]. The mechanism by which RJ exerts its longevity effects on queen bees and the identities of the components that play critical roles in this process are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, using the ECL detector previously proposed by Chiang et al [65], trimethylamine, an indicator of spoiling in fish, has been sensitively determined [77]. In addition, acetylcholine was detected in royal jelly by previous decomposition into trimethylamine when it was heated to its melting point [78]. Other applications involved the detection of monosaccharides in herbs, using 2-diethylaminoethanethiol as a derivatizing reagent [79], herbicides, such as glyphosate and its major metabolite aminomethylphosphonic acid in soybean [80] or guava fruit [81], or the determination of antibiotic residues used in veterinary medicine, such as enrofloxacin and its metabolite cirpofloxacin in milk, with detection limits lower than the maximum residue limits legislated by European regulations [82].…”
Section: Food and Environmental Applicationsmentioning
confidence: 99%